Comparative Raman scattering study of Ba3MSb2O9 (M=Zn, Co and Cu) - Glamazda, A.; Lemmens, P.; Do, ,S.-H.; Choi, K.-Y. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2017)
Raman spectroscopy is combined with lattice dynamic calculations to investigate the magnetic and structural properties of the 6H-perovskite compounds Ba3MSb2O9 (M = Zn, Co and Cu). Unlike the nonmagnetic Ba3ZnSb2O9 compound, the magnetic counterparts Ba3MSb2O9 (M = Co and Cu) show both lattice anomalies for temperatures below 100 K and develop highly correlated spin states below 50 K. This is ascribed to an instability of сonventional magnetic excitations for the equilateral triangular antiferromagnet Ba3CoSb2O9 and a co-existence of spin-orbital liquid and random singlet state for the decorated honeycomb compound Ba3CuSb2O9 containing a nearly identical volume fraction of hexagonal and orthorhombic phases. Our results demonstrate that Ba3MSb2O9 provides a rich reservoir for hosting diverse magnetic and structural phases as a function of the metal ion M.